(untitled) (PJDOL, 2023)
The study aimed to find out relationship between satisfaction and learning style of distance learners enrolled at M.Ed. program at Allama Iqbal Open University Islamabad. It was a co relational study and was carried out by selecting a sample of 351 students through stratified random sampling procedure. Students’ satisfaction was measured by using student Satisfaction Survey developed by Strachota (2006) while their learning style was assessed using Grasha-Riechmann Student Learning Styles Scale.